Contribution of Agility and Flexibility to Football Dribbling Skills in Junior High School Extracurricular Students - Mirza Asmara; Wawan Indrawan; Ali Munir; Zanzabil Adwa Fitrian; Naufallathuf Yaquttul Isrsyad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Dribbling is a basic engineering skill most often used by football players in both amateur and professional classes. Because with dribbling therapy, it can help the effort to score goals into the opponent's goal as the ultimate goal of the football game. This study aims to find out the magnitude of the contribution between agility to dribbling ability in extracurricular football students, then find out the magnitude of the contribution between flexibility to dribbling ability in extracurricular football students of SMP N 2 Liwa, as well as to know the magnitude of the contribution between agility and flexibility to the dribbling ability of football extracurricular students. The sample of this study was 30 junior high school extracurricular students with male gender. The method used is descriptive correlational, which is a study that aims to describe or describe events or events that are taking place at the time the research is carried out without regard to before and after with a validity value of 0.67, and test reliability of 0.79. The results of this study are Agility contributes to dribbling skill results by 50.12%, while the rest is influenced by other variables, flexibility contributes to dribbling skill results by 28.19%, while the rest is influenced by other variables, agility and flexibility contribute to dribbling skill results by 55.65%. Keywords: agility, flexibility, dribbling skills, students.